Numerical study on subcooled water jet impingement cooling on superheated surfaces - Moon, Joo Hyun; Lee, Soyeong; Lee, Jungho; Lee, Seong Hyuk (Case Studies in Thermal Engineering, 2022)
The present study aims to numerically investigate the rapid cooling heat transfer characteristics of the superheated solid surfaces when the subcooled water jet impinges. The computational fluid dynamics (CFD) simulation was carried out by considering boiling and condensation heat transfer to estimate key design parameters such as wall heat flux, heat transfer coefficient, and surface temperature variation using the volume-of-fluid (VOF) model. The simulated results agreed well with the experimental data of the surface temperature and the wall heat flux at the stagnation point. The water vapors formed near the stagnation point and rapidly propagated radially after impact. Also, strong vorticity was found in a radial direction, resulting in a vapor blanket. The result showed that the vapor blanket prevented the liquid flows from directly contacting the heated surface, decreasing the heat transfer. In particular, the surface temperature in the radial direction cooled down more rapidly than that in the vertical direction because of higher boiling heat transfer within a wetting radius where the heat transfer coefficient became higher owing to the liquid wetting.
Keywords: Boiling heat transfer; Heat transfer co-efficients; Jet impingement cooling; Radial direction; Stagnation points; Sub-cooled water; Subcooled water jet impingement; Surface temperatures; Wall heat flux; Water jets impingement; Boiling; Computational fluid dynamics; Heat flux; Subcooled water jet impingement